Personal shopper [videorecording (DVD)] - Assayas, Olivier; Stewart, Kristen, 1990-; Eidinger, Lars, 1976-; Bouaziz, Sigrid (Criterion collection, 2017)
This evocative character study tells the story of a young American fashion assistant and spiritual medium who is living in Paris and searching for signs of an afterlife following the sudden death of her twin brother. A stirring depiction of grief in the form of a psychological thriller, and a chilling meditation on modern modes of communication and the way we mourn those we love.